Larval development of Hexapanopeus paulensis Rathbun, 1930 (Crustacea, Brachyura, Xanthidae) under laboratory conditions - Fransozo, Adilson [UNESP]; Mantelatto, Fernando Luiz Medina [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Sociedade Brasileira de Zoologia, 1990)
Four zoeal stages and one megalopa stage of Hexapanopeus paulensis Rathbun, 1930 were obtained from eggs of ovigerous females from the northern coast of São Paulo State, Brazil. The experiments were performed in a climatically controlled room at 24 ±1 ºC at a salinity of 34.5%, and the animals were fed with newly hatched Artemia salina nauplii. All larval stages are illustrated and described in detail. The complete larval development consists of 4 zoeal stages and 1 megalopal stage. The main morphological characters that allow the identification of the zoeae and megalopa of H. paulensis are analyzed with respect to the other species of Xanthidae's family from southern and southeastern Brazilian coast.